Geochemical signatures of recent bar deposits in the Tista river, Bangladesh: Implications to provenance, paleoweathering and tectonics (Journal of Nepal Geological Society, 2020)
Petrography and geochemical composition of sediments is a sensitive indicator which archives the signature of a previous record of a source rock and depositional environments in a basin.  This study deals with the elemental geochemistry of recent bar deposits of the Tista river in the north western part of Bangladesh to evaluate their provenance, paleoweathering and tectonic setting. Petrographically, the sediments are rich in quartz (70%), whereas feldspar and lithic fragments are found about 8% and 3%, respectively. The geochemical composition of the samples exhibits dominantly quartzose litharenites with low grade sedimentary and metasedimentary lithics, low feldspar indicates tectonic provenance field of recycled orogeny. Discrimination functions revels that the sediments of the Tista river are the derivation of active continental margin. The analyses also reflect that the sediments are dominantly a mixture of felsic (e.g., granitic/Gneiss, quartzite, amphibolite, granulite facies rock types) and some of mafic source (e.g., alkali-basalt/greenschist facies). It may occur, since 60% of the sedimentary flux carried out by the river from low-grade metamorphic rock and the rest from high-grade rock (in the west and north Sikkim Himalaya respectively). The weathering indices highlight that the source rocks have not undergone significant chemical weathering. The immature sorting status and petrographic evidences indicate that the sediments deposited in the Tista river basin are simply the product of mechanically weathered rocks.